CHALLENGES AND SOLUTIONS IN EVALUATION OF ISLAMIC EDUCATION - Umar; Nuril Huda; Dina Hermina; Agustina Rahmi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Islamic Education Evaluation has many challenges. The author lists three of them. The first is that each student has different needs and learning styles. The second is that not all teachers can carry out proper and objective evaluation well. The third is cultural differences. This study aims to find out 1.identification of challenges in Islamic education evaluation 2.solutions to overcome challenges in Islamic education evaluation. This research uses qualitative-descriptive-literature method with data collection techniques including documentation such as books and journals. The author writes 3 (three) solutions to the 3 (three) challenges. The first is the suitability of the evaluation tool. Second is the standard for objectivity so as not to bias the evaluation. Third is a number of values related to cultural differences, namely tasamuh (tolerance), ta'awun (mutual help), and tawazun (harmony).